MEK reduces cancer-specific PpIX accumulation through the RSK-ABCB1 and HIF-1α-FECH axes - Vipin Shankar Chelakkot (Nature Portfolio, 2020)
Abstract The efficacy of aminolevulinic acid (5-ALA)-based photodynamic diagnosis (5-ALA-PDD) and photodynamic therapy (5-ALA-PDT) is dependent on 5-ALA-induced cancer-specific accumulation of protoporphyrin IX (PpIX). We previously reported that inhibition of oncogenic Ras/MEK increases PpIX accumulation in cancer cells by reducing PpIX efflux through ATP-binding cassette sub-family B member 1 (ABCB1) and ferrochelatase (FECH)-catalysed PpIX conversion to haem. Here, we sought to identify the downstream pathways of Ras/MEK involved in the regulation of PpIX accumulation via ABCB1 and FECH. First, we demonstrated that Ras/MEK activation reduced PpIX accumulation in RasV12-transformed NIH3T3 cells and HRAS transgenic mice. Knockdown of p90 ribosomal S6 kinases (RSK) 2, 3, or 4 increased PpIX accumulation in RasV12-transformed NIH3T3 cells. Further, treatment with an RSK inhibitor reduced ABCB1 expression and increased PpIX accumulation. Moreover, HIF-1α expression was reduced when RasV12-transformed NIH3T3 cells were treated with a MEK inhibitor, demonstrating that HIF-1α is a downstream element of MEK. HIF-1α inhibition decreased FECH activity and increased PpIX accumulation. Finally, we demonstrated the involvement of RSKs and HIF-1α in the regulation of PpIX accumulation in human cancer cell lines. These results demonstrate that the RSK-ABCB1 and HIF-1α-FECH axes are the downstream pathways of Ras/MEK involved in the regulation of PpIX accumulation.